Aspects of linguistic fieldwork in the German colonial era (Linguistics in Amsterdam, 2014)
When explorers, missionaries or government employees were sent to former German colonial territories at the turn of the 20th century, one of the main objectives was to record and describe local vernaculars. As many of these travellers had little or no knowledge about languages other than their own, there was an urgent need for instruction in linguistic fieldwork. This article focuses on this special type of colonial writing as these instructional texts are a very promising object for research for at least two reasons: first their guiding function enabled them to act as multipliers for the common knowledge on language studies. Investigating these manuals can therefore reveal how language ideologies conveyed by them have shaped linguistic documentation in the colonial context. This of course had a strong influence on any common thinking about these languages in the metropolis. Furthermore, when studied in chronological order, the manuals yield valuable insights into the development of fieldwork methodology.